Sucessão da comunidade fúngica termofílica e termotolerante na compostagem da gordura de frango - Monteiro, Lana Sobral Vieira Escada [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Composting is a popular sustainable alternative for final waste disposal. Fungi and bacteria are the main drivers of this process, because they are the ultimate decomposers of the organic matter. However, few studies explored how the thermophilic and thermotolerant fungi (the ones that can resist high temperature) are involved in composting. Assessing the composition and dynamics of such fungal communities can be helpful for developing products to accelerate the composting of many residues. The high biological digestion system (ADB) uses such an accelerator to increase the decomposition rate. Here we evaluate the succession of the thermophilic and thermotolerant fungi in the composting process of residues derived from a poultry slaughterhouse. A total of four samples from the decomposing material were collected for fungal isolation, each representing one stage of the composting process. Classic and molecular (DNA sequencing) methods were used to identify the isolated microorganisms. Fungal communities found were evaluated for richness and abundance of taxa in each stage of the process. The initial raw substrate (sawdust) had a greater number of fungi when compared to substrate in the mesophilic phase, considering the colony forming units per gram of sample. The fungal abundance increased again during the thermophilic phase and remained stable until the end of the process. A total of 74 heat resistant fungi were isolated comprehending five taxa: Rhizomucor sp. (representing 54.1 % of the isolated fungi), Aspergillus fumigatus (29.7 %), Lichtheimia sp. (6.8 %), Rhizopus sp. (5.4 %) and Thermomyces sp. (4.1 %). Aspergillus fumigatus and Rhizomucor sp. were observed in all stages, representing 100 % of the isolated fungi at the thermophilic phase. On the other hand, Thermomyces sp. and Rhizopus sp. were isolated from the initial substrate and in the mesophilic stage. This result points to a decrease of fungal richness during the thermophilic stage...

A compostagem é uma alternativa comum e sustentável para a disposição final de resíduos sólidos. Fungos e bactérias são os principais atuantes nesse processo, uma vez que realizam a decomposição da matéria orgânica. A participação dos fungos termofílicos e termotolerantes (i. e. aqueles que resistem a altas temperaturas) na compostagem é pouco estudada. A compreensão da composição e da dinâmica das comunidades desses microorganismos possibilita desenvolver aceleradores para a compostagem de diversos tipos de resíduos. O sistema de compostagem de Alta Digestão Biológica (ADB) utiliza de tal acelerador para aumentar a taxa de decomposição. O presente trabalho avaliou a sucessão das comunidades fúngicas na compostagem da gordura de frango utilizando esse sistema. Foram coletadas amostras do resíduo em decomposição nas diferentes fases da compostagem para isolamento dos fungos termofílicos e termotolerantes. Utilizando técnicas clássicas e moleculares (sequenciamento de DNA), foi realizada a identificação desses microorganismos. As comunidades fúngicas foram avaliadas quanto à riqueza e abundância de taxa nas diferentes fases do processo. O substrato inicial (serragem) apresentou maior quantidade de fungos termofílicos e termotolerantes, quando comparado à fase mesofílica do processo, considerando as unidades formadoras de colônias por grama de amostra. A quantidade desses fungos voltou a aumentar durante a fase termofílica e a carga fúngica manteve-se estável na fase de maturação do composto. Foram obtidos 74 isolados de fungos resistentes ao calor. Desse total, foi possível identificar cinco taxa: Rhizomucor sp. (compreendendo 54,1 % do total de isolados), Aspergillus fumigatus (29,7 %), Lichtheimia sp. (6,8 %), Rhizopus sp. (5,4 %) e Thermomyces sp. (4,1 %). Os fungos A. fumigatus e Rhizomucor sp. ocorreram em todas as fases do processo, sendo que na termofílica representaram...
Keywords: Fungos; Microorganismos termofilicos; Adubos compostos; Resíduos; Resíduos sólidos; Degradação ambiental